Vegetable Production in Ukraine in the Context of Economic Instability: Forecast and Future Prospects - Gutsul, Tetiana (Здобутки економіки: перспективи та інновації, 2025)
The agricultural sector of Ukraine is currently one of the few sectors of the economy that, despite the significant problems of the state’s financial development in the context of the war, demonstrates relative functioning stability. In line with food traditions and the availability of fertile land in Ukraine, the vegetable growing industry is well developed, accounting for about 20% of total agricultural production in Ukraine. The outbreak of a full-scale war on the territory of Ukraine poses challenges to vegetable producers. It requires them to intensify their efforts to maintain production capacity and use their development potential even in difficult economic conditions. The purpose of the article is to determine the impact of economic instability caused by the war on vegetable production in Ukraine, as well as to assess the prospects for the development of the industry in the face of current challenges. The study uses statistical analysis and SWOT analysis to systematise the strengths and weaknesses of the industry and identify opportunities and threats. The analysis showed that in the pre-war period, vegetable production was actively developing, providing significant exports and creating a positive image of Ukraine in international agricultural markets. However, the full-scale war significantly complicated the functioning of producers due to the disruption of logistics chains, lack of financial resources and occupation of large areas. The main weaknesses of the industry are its dependence on weather conditions, outdated equipment, and high credit costs. At the same time, its strengths include significant resource potential, a developed transport system, and government support. The survey results show that development prospects depend on the dynamics of hostilities. Key opportunities include participation in grant programmes, export development and modernisation of production technologies. Threats include the duration of hostilities, rising inflation, and limited access to resources. The conclusions emphasise the need to strengthen state regulation, support domestic producers and use modern technologies to ensure food security in Ukraine.